Immunitet państwa: instytucja na rozdrożu prawa - Muszyński, Mariusz; Osiejewicz, Joanna (Polski Przegląd Stosunków Międzynarodowych, 2018)
The article attempts to identify and explain the character and scope of state immunity in contemporary international law. It was assumed and proved that the centre of gravity of immunity protection had started to gradually change its place to justify the immunity not only from a stato-centric but also from an anthropocentric perspective. This process is neither linear nor predictable and it raises doubts, whose rights shall be protected by the immunity and which perspective shall prevail. The research is concerned with determining the existing scope of state immunity and when it can be excluded. The article introduces the phenomenon of state immunity as a rule of law and defines the subjective and objective scope of this institution. Next, the circumstances under which the immunity is excluded are briefly described, in particular the consent of the state to submit to jurisdiction as well as the criteria for the exclusion of the immunity under legal regulations. Then the results of the analysis of judicial decisions on state immunity are provided. The cited judgments are sorted into two groups: those treating the immunity mostly from the viewpoint of a human being as a subject of rights and obligations under international law and those passed in a spirit of preserving friendly relationships among states whilst justifying the immunity from the viewpoint of a sovereign.